Study on Effectiveness of Fuzzy Set Theory through its Practical Application (Patan Pragya, 2022)
This paper deals with the poverty as a main problem of our country Nepal. The Government wants to solve this problem by definite rule. The line of demarcation of defining the jurisdiction of the collection of poverty-stricken people does not exist. However, it is obvious that certain vague demarcation must exist in order to divide the resources as needed. In this paper, I have applied the fuzzy set of poverty-stricken Nepali as the function A: N→ [0, 1].